Knowledge creation through collaboration: The role of shared institutional affiliations and physical proximity. (22nd May 2021) - Stephens, Bryan; Cummings, Jonathon N.
Abstract: This paper examines how shared affiliations within an institution (e.g., same primary appointment, same secondary appointment, same research center, same laboratory/facility) and physical proximity (e.g., walking distance between collaborator offices) shape knowledge creation through biomedical science collaboration in general, and interdisciplinary collaboration in particular. Using archival and publication data, we examine pairwise research collaborations among 1, 138 faculty members over a 12‐year period at a medical school in the United States. Modeling at the dyadic level, we find that faculty members with more shared institutional affiliations are positively associated with knowledge creation and knowledge impact, and that this association is moderated by the physical proximity of collaborators. We further find that the positive influence of disciplinary diversity (e.g., collaborators from different fields) on knowledge impact is stronger among pairs that share more affiliations and is significantly reduced as the physical distance among collaborators increases. These results support the idea that shared institutional affiliations and physical proximity can increase interpersonal contact, providing more opportunities to develop trust and mutual understanding, and thus alleviating some of the coordination issues that can arise with higher disciplinary diversity. We discuss the implications for future research on scientific collaborations, managerial practice regarding office space allocation, and strategic planning of initiatives aimed at promoting interdisciplinary collaboration.